The Impact of Central Bank FX Interventions on Currency Components - Michel Beine; Charles S. Bos; Sebastian Laurent (Tinbergen Institute, 2005)
This paper is the first attempt to assess the impact of official FOREX interventions of the three major central banks in terms of the dynamics of the currency components of the major exchange rates (EUR/USD and YEN/USD) over the period 1989-2003. We identify the currency components of the mean and the volatility processes of exchange rates using the recent Bayesian framework developed by Bos and Shephard (2004). Our results show that in general, the concerted interventions tend to affect the dynamics of both currency components of the exchange rate. In contrast, unilateral interventions are found to primarily affect the currency of the central bank present in the market. Our findings also emphasize a role for interventions conducted by these central banks on other related FOREX markets.
Keywords: C11; C32; E58; F31; 330; Central banks; interventions; exchange rates; stochastic volatility; state space